What causes the college attendance gap in Korea? - Lee, Seung-Eun (KDI School, 2011)
This paper aims to investigate which factor would be more important in constraining 4-year college attendance in Korea: short-term unaffordability to pay college tuition fees and the long-term disadvantaged family backgrounds that are crystallized in poor academic achievement. According to the regression results, family income at the college going ages has little effect on 4-year college attendance while family income at earlier ages and academic performance in middle school have significant effect. Also, following the methodology used by Heckman and his collaborators who previously performed similar research on the cause of the U.S.’s higher education gap, I suggest that the more crucial constraint is their academic performance gap caused by long-term family background. This result provides important policy implication to current situation where most policy-setting discussions to alleviate higher education gap focus only on lowering college tuition fees.
Thesis(Master) --KDI School:Master of Public Policy,2011